Assessing access barriers to Tuberculosis (TB) and Antiretroviral (ARV) treatment in Mitchell's Plain, Cape Town South Africa - Mweemba, Chrispin (Health Economics Unit, 2015)
Access to health care is a very important concept which has equally important implications to the health status of individuals. However, there have been a lot of debates among researchers and policy makers on what constitutes access, and how it can be made less conceptual and more operational. The concept of access has continued to receive increased attention because of a growing realisation of its importance in health policy. Furthermore, provision of services alone without understanding barriers individuals face in accessing services could result in less optimal outcomes. It is therefore necessary to have an understanding of what "access" entails and factors that influence it if we are to have a real chance of improving access to health services and therefore enhance health. In this thesis access is viewed as consisting of three (3) interrelated and measurable dimensions (availability, affordability and acceptability). These access dimensions are related to both the system and user characteristics. Access is therefore said to have been achieved when all the three dimensions have been satisfied. Using the above definition of access, the main focus of this thesis is on access barriers (in relation to the three access dimensions) to both Tuberculosis (TB) and Antiretroviral Treatment (ART) services in Mitchell's Plain, Cape Town South Africa. Secondary cross-sectional data was used for this purpose. Access to TB and HIV treatment has been given priority because the two diseases have had a massive and negative impact on public health in the country. In addition, patients using these services may face similar barriers to care. Findings of this thesis are expected to provide insights into the barriers TB and HIV patients face in seeking care vis-a-vis availability, affordability and acceptability of services. Findings will therefore prove valuable in as far as improving access is concerned.